2011
DOI: 10.1590/s1808-86942011000500002
|View full text |Cite
|
Sign up to set email alerts
|

Study on suppression of otoacoustic emissions: lateral domain

Abstract: A pon stimulation by contralateral, ipsilateral or bilateral noise, the medial olivocochlear efferent tract changes the amplitude of otoacoustic emissions relative to the tested ear, reducing or removing it; this resulted in a reduction/suppression effect of otoacoustic emissions. Differences in patterns of elimination/reduction of otoacoustic emissions between ears have been documented worldwide; there are, however, no Brazilian studies investigating the effect of lateral dominance. Aims:To compare the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Our results showed no significant effect of the ear of presentation of the CS on the change in sharpness of the PTCs produced by the CS. As described in the Introduction section, some studies showed a greater effect of CS on TOAEs when the CS was presented to the left ear than when it was presented to the right ear (Khalfa et al, 1998;Perrot et al, 1999), but such an asymmetry has not always been found (de Oliveira et al, 2011). Brashears et al (2003) found a nonsignificant trend for the effect of the CS to be greater for musicians than for nonmusicians when the CS was presented to the left ear, but our results revealed no such trend.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed no significant effect of the ear of presentation of the CS on the change in sharpness of the PTCs produced by the CS. As described in the Introduction section, some studies showed a greater effect of CS on TOAEs when the CS was presented to the left ear than when it was presented to the right ear (Khalfa et al, 1998;Perrot et al, 1999), but such an asymmetry has not always been found (de Oliveira et al, 2011). Brashears et al (2003) found a nonsignificant trend for the effect of the CS to be greater for musicians than for nonmusicians when the CS was presented to the left ear, but our results revealed no such trend.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the effect of CS on TOAEs is greater when the evoking stimulus is presented to the right ear and the CS is presented to the left ear than vice versa (Bidelman & Bhagat, 2015; Khalfa et al., 1998), although such an effect has not always been found (de Oliveira et al., 2011). The asymmetry, when present, appears to be similar for musicians and nonmusicians (Perrot et al., 1999), although Brashears et al.…”
mentioning
confidence: 99%
“…Although the difference is not statistically significant, this result suggests lower effectiveness of the medial efferent olivocochlear system concerning the EG 7,13. . Numerical comparisons between studies are difficult, since there are methodological differences used to measure the suppression of TEOAEs, such as type and intensity of suppressive noise, intensity and polarity of the click, and the ear in which the masking was presented (contralateral/ipsilateral/bilateral) and the equipment used 27 . This study did not show statistically significant differences between the presence of suppression and age in the EG individuals (Table 3), although previous studies have demonstrated a reduction in the suppression effect according to age increases 28,29 .…”
Section: Legend: Teoaes-transient-evoked Otoacoustic Emissions N -Nummentioning
confidence: 99%
“…7 15 17 As a consequence, the effect of suppression of evoked OAEs is characterized by a reduction in the response amplitude or by latency and phase changes when a contralateral noise is introduced simultaneously to the recording. 18 …”
Section: Review Of the Literaturementioning
confidence: 99%